PROSES MANAJEMEN STRATEGI DI SEKOLAH DASAR SWASTA ADHYAKSA II MEDAN - Dian Pratiwi Br. Marpaung; Nurroyian; Rama Satya Tanjung; Ahmad Mukhlasin (Journal of International Multidisciplinary Research, 2023)
The strategic management process plays an important role in improving the quality of education in schools. By implementing an effective strategic management process, schools can identify and implement appropriate steps to achieve the desired educational goals. The research results show that implementing an effective strategic management process can help schools identify potential and challenges in achieving their educational goals. This process involves steps such as formulating a clear vision and mission, identifying specific educational needs, establishing priority strategies, allocating resources effectively, and conducting regular monitoring and evaluation. This research aims to understand how the strategic management process can be implemented effectively in schools in order to improve the quality of education. The research method used is a case study by taking one school as a sample. Data was collected through interviews with teachers through direct observation in the school environment.